PENGARUH SKEPTISISME PROFESIONAL AUDITOR, KOMPETENSI, INDEPENDENSI DAN KOMPLEKSITAS AUDIT TERHADAP KUALITAS AUDIT - Nugrahaeni, Suci; Samin, Samin; Nopiyanti, Anita (Department of Accounting, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta, 2018)
This study was conducted with the aim to examine the influence of The Auditor’s Professional Skepticism, Competence, Independence and Complexity of The Audit on Audit Quality. The sample used in this study is 70 auditor by using purposive sampling method. The analysis technique that used in this study is multiple linear regression with significance level of 5%. The results of this study indicate that the value of Adjusted R Square is 0.547 or 54,7% which means that the ability ofindependent variables namely the Auditor’s Professional Skepticism, Competence, Independence and Complexity Audit in explaining the dependent variable that is Audit Quality is 54,7% and the rest 45,3%is explained by other variables outside of that variables used in this study. The results of this study also show that (1) The Auditor’s Professional Skepticism has significant effect on Audit Qualitybecause it has a significance value lower than the level of significance of 5% that is equal to 0,002 or 0,2% (2) Competence has significant effect on Audit Quality because it has a significance value lower than the level of significance of 5% that is equal to 0,024 or 2,4% (3) Independence has no significant effect on Audit Quality because it has a significance value greater than the level of significance of 5% that is equal to 0,610 or 61% (4) Complexity of The Audit has no significant effect on Audit Quality because it has a significance value greater than the level of significance of 5% that is equal to 0,341 or 34,1%.